2020
DOI: 10.1021/acschembio.9b01036
|View full text |Cite|
|
Sign up to set email alerts
|

Studies of Thioamide Effects on Serine Protease Activity Enable Two-Site Stabilization of Cancer Imaging Peptides

Abstract: Thioamide substitutions in peptides can be used as fluorescence quenchers in protease sensors and as stabilizing modifications of hormone analogs. To guide these applications in the context of serine proteases, we here examine the cleavage of several model substrates, scanning a thioamide between the P3 and P3′ positions, and identify perturbing positions for thioamide substitution. While all serine proteases tested were affected by P1 thioamidation, certain proteases were also significantly affected by other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 26 publications
(58 reference statements)
1
30
0
Order By: Relevance
“…Fluorescent quenchers, such as thioamides, can be used to track and reduce proteolytic degradation, thus stabilizing and increasing the in vivo serum half-life of peptides. 37 , 38 Cysteine protease can be tracked through the synthesis of thioamide-labeled peptides. 39 When the peptide is cleaved, the thioamide group stops quenching and fluorescence can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent quenchers, such as thioamides, can be used to track and reduce proteolytic degradation, thus stabilizing and increasing the in vivo serum half-life of peptides. 37 , 38 Cysteine protease can be tracked through the synthesis of thioamide-labeled peptides. 39 When the peptide is cleaved, the thioamide group stops quenching and fluorescence can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously observed similar multiple-site stabilization with thioamide substrates of serine proteases, which we were able to exploit to stabilize cancer cell imaging peptides at two positions with a single thioamide modication. 22 Overall, having a thioamide at the P1 position here rendered the K S 3A and R S 3A peptides completely resistant to proteolysis by Cts V, Cts K, and Cts S, while signicantly slowing the rate of proteolysis by Cts L (Table 1). The only exception to this P1 thioamide effect was with Cts B, where the K S 3A and R S 3A peptides were cleaved at the penultimate C-terminal alanine residue as indicated by the slashes -mHLFK S AA/Am or mHLFR S AA/Am (Tables S7, S9 and Fig.…”
Section: Resultsmentioning
confidence: 84%
“…21 Motivated by these results showing thioamide stabilization effects at P2 and P1 positions (positions numbered from the scissile bond by convention), our laboratory developed a uorescence sensor design to systematically study the positional effects of thioamide substitution against different cysteine proteases (papain, cathepsins L, V, K, B, and S) and serine proteases (trypsin, chymotrypsin, and kallikrein). [22][23][24] Intriguingly, we found that thioamide positional effects differ not only between serine proteases and cysteine proteases, but also between members of the same protease family despite their high homology (31-59% sequence identity) and mechanistic similarity. 22,24 We also successfully utilized data from these systematic studies to design a two-site stabilized thioamide peptide specically targeting neuropeptide Y 1receptor expressing MCF-7 breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, thioamides have been used in a variety of biochemical contexts, including conformational stabilization of peptide macrocycles, [6] conferring protease resistance to peptides, [7] and as fluorescence turn-on probes for proteases. [8][9][10] However, it has also been shown that thioamide substitution in the backbone can have negative effects on protein stability. [11] Additionally, positioning of thioamides near the scissile bond of protease substrates must be evaluated carefully.…”
Section: Introductionmentioning
confidence: 99%